1973
DOI: 10.1002/cne.901520302
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the cat olfactory bulb

Abstract: The fine structure of the olfactory bulb was investigated in the cat. Five types of bulbar neurons were identified on the basis of size, location, cytoplasmic organelles and synaptic complexes with the neuron perikaryon. The smallest diameter neurons were predominantly located in the glomerular and granule cell layers. Ultrastructural characteristics for these two neuron populations, viz., periglomerular and internal granule cells, were identical. Tufted cells, smaller in diameter than mitral cells, were locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…These cells are probably also not Schwann cells even though Willey (1973) has referred to them as such. Schwann cells are typically enclosed by basal laminae and collagen fibers (Causey, 1960;Glees and Meller, 1968;Peters et al, 1976;Carlsen and Behse, 1980), whereas ensheathing cells were not apposed to basal laminae except in those places where they formed part of the external glial limiting membrane.…”
Section: Identification Of Ensheathin-g Cells In Thementioning
confidence: 99%
“…These cells are probably also not Schwann cells even though Willey (1973) has referred to them as such. Schwann cells are typically enclosed by basal laminae and collagen fibers (Causey, 1960;Glees and Meller, 1968;Peters et al, 1976;Carlsen and Behse, 1980), whereas ensheathing cells were not apposed to basal laminae except in those places where they formed part of the external glial limiting membrane.…”
Section: Identification Of Ensheathin-g Cells In Thementioning
confidence: 99%
“…Electron microscopic studies of the olfactory bulb have revealed reciprocal synapses between mitral cell dendrites and the peripheral processes of granule cells (Fig. 1B and C) (Hirata, 1964;Andres, 1965;Rall et al 1966;Price & Powell, 1970a;Reese & Shepherd, 1972;Willey, 1973). Moreover, it has been reported that nearly all the synapses found on mitral cell dendrites and somata, except in or around the glomerular region, are reciprocal synapses with the peripheral processes of granule cells (Price & Powell, 1970b; Reese & Shepherd, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Early electron microscopic studies focused on neuronal elements, especially intraglomerular synapses, and noted the presence only of astroglial tissue components (Reese and Brightman, 1965;Powell, 1971b, 1972;Willey, 1973). Later, astrocytes were identified morphologically by Golgi staining, histochemically by silver-carbonate impregnation, and immunohistochemically by glial fibrillary acidic protein (GFAP) antibodies.…”
mentioning
confidence: 99%